Towards energy-efficient RO-PRO systems: impact of PRO spiral wound membrane module design on power density and energy consumption - Ng, W.H.; Liang, Y. Y.; Fimbres Weihs, G. A. (Elsevier Ltd, 2025)
Modeling spiral wound membranes (SWMs) in pressure retarded osmosis (PRO) systems is challenging due to complex flow patterns, non-uniform pressure and concentration distributions, and non-linear water flux behavior. This paper develops a SWM module-scale model to evaluate the specific energy consumption (SEC) of the RO-PRO hybrid desalination process, showing good agreement with reported module-scale water flux. An enhanced metric for estimating the minimum SEC in RO-PRO system is proposed. The breakdown of energy losses identifies inefficiencies in the energy recovery device and pump as the main contributors to diminished PRO SWM performance, followed by concentration polarization and friction losses in the draw and feed channels. The validated model is used to analyze the effects of SWM channel height, membrane length and width, on both power density (PD) and SEC. A 4-fold increase in PRO membrane area, either by extending membrane length (adding modules), improves energy harvesting and reduces desalination SEC by up to 2.2 %. However, this also leads to a ∼1 % decrease in PD. Furthermore, the optimized PRO-SWM design characteristics are elucidated. Reducing membrane area increases PD by concentrating power output, but at the expense of higher SEC due to limited water permeation.